Association of chronic viral hepatitis with ABO blood groups and rhesus (Rh) factor - Shakeel, Hassan Abdullah; Maqsood, Hamza; Ali, Basit; Khan, Ali Raza (International Journal of Research in Medical Sciences, 2018)
Background: Chronic viral hepatitis includes hepatitis B and hepatitis C and is responsible for causing the deaths of millions of people all across the world each year. Although there are small studies in literature about association between ABO blood groups and chronic viral hepatitis, only few studies found relation between them. The objective of this case control study is to establish a relation between the host factors and these viral infections. Methods: This is a case control study on patients diagnosed with CVHB and CVHC. The study was conducted on 508 patients reported to Nishtar Hospital, Multan and Sheikh Zayd Hospital, Rahim Yar Khan, Pakistan.709 healthy blood donors were selected as a control group from Nishtar Hospital blood bank during December 2016 and December 2017.The results were subjected to SPSS v.20 for analysis using the chi square test. The patients and blood donors were also asked about certain demographic factors like age, sex and blood transfusions. Results: Among CVHB patients,173(100%), the distribution of blood groups was following: Group A, 38 (21.96%), B, 57 (32.94%), AB, 11 (6.35%), O, 67 (38.72%). 158 (91.32%) were Rh positive and 15 (8.67%) Rh negative. In CVHC patients, 335 (100%), the distribution was following: Group A, 69 (20.59%), B, 123 (36.71%), AB, 24 (7.16%), O, 119 (35.52%). 303 (90.44%) were Rh positive while 32 (9.55%) were Rh negative. In healthy blood donors, 167 (23.55%) were group A, 225 (31.73%) group B, 41(5.78%) group AB, 276 (38.92%) group O.632 (89.13%) were Rh positive and 77 (10.86%) Rh negative. Conclusions: There was no significant difference between blood groups(p>0.5) and Rh(p>0.5) with chronic viral hepatitis. However, it was also observed that the infections of HCV increase among (26-45) years old patients while the HBV infections increase with progression of age. Association of chronic viral hepatitis infection with blood group types needs more studies to get more knowledge about this aspect.